Acute fatty liver of pregnancy: cases series and review of the literature - Hamdoun, Sara; Serhane, Salim; Moustaide, Houda; Benkirane, Saad (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Acute fatty liver of pregnancy (AFLP) is a condition that occurs during the third trimester of pregnancy, typically manifesting around 36 weeks of gestation. It represents a critical obstetric emergency with considerable neonatal mortality. To manage AFLP disease, a multidisciplinary approach is essential which helps meaningfully in the improvement of its prognosis during the post-partum period. Historically, it was considered a fatal disease for both mother and fetus. Nowadays, the prognosis is improved by rapid diagnosis, early delivery and administration of treatment. We reported three cases of Moroccan women diagnosed with AFLP in our hospital who received a multi-disciplinary care with good prognosis. The first and third parturient gave birth by vaginal delivery and the second one by caesarean section.